Spatial distribution of metallic heteroatoms in soot nanostructure mapped by aberration-corrected STEM-EELS. (March 2021) - Wiinikka, Henrik; Hage, Fredrik S.; Ramasse, Quentin M.; Toth, Pal
Abstract: Soot from the thermochemical conversion of solid and liquid fuels can be infused with metallic heteroatoms originating from the fuel – these heteroatoms alter the nanostructure and the reactivity of the soot. Here, we investigate the spatial distribution of metallic heteroatoms in soot generated by biomass gasification, using aberration-corrected Scanning Transmission Electron Microscopy and Electron Energy Loss Spectroscopy (STEM-EELS). The technique allowed for the mapping of heteroatom distribution in soot at the nanoscale, and thereby for the direct correlation of heteroatom concentration with the graphitic nanostructure. Spherical soot particles were coated with a thin layer of silicon, possibly in the form of quartz that may be linked to minor distortions of the nanostructure of the graphitic shell of the particles. Further results on non-spherical soot and inorganic-carbon fused aggregates suggest that the chemistry of formation was affected by the presence of gaseous ash-forming elements, especially calcium, with carbon-oxygen functional groups forming as intermediates in the graphite-inorganic reaction; i.e., prior to the formation of the thermodynamically stable carbonate bonds. The analytical approach demonstrated here can potentially help select fuel additives or aid in the design of fuel blends that minimize the formation of similar, hybrid carbon nanoparticles in combustion or gasification systems. Graphical abstract: Image 1 Highlights: Metal infused soot particles were analyzed with aberration-corrected STEM-EELS. Spherical soot particles were coated with silicon and oxygen, possibly quartz. Calcium affect the graphitic structure of non-spherical soot. Carbon-oxygen functional groups could be detected in non-spherical soot. STEM-EELS can help understand particle formation mechanisms.